Обгрунтування технології виробництва яловичини за використання абердин-ангуської худоби у східному регіоні України - Колісник, Олександр Іванович (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня доктора сільськогосподарських наук за спеціальністю 06.02.04 «Технологія виробництва продуктів тваринництва». Національний університет біоресурсів і природокористування України. Київ, 2018. Дисертаційна робота присвячена обґрунтуванню ресурсоощадної технології виробництва яловичини за використання абердин-ангуської породи великої рогатої худоби у східному регіоні України. Переглянуто низку теоретичних і практичних положень щодо виробництва яловичини у м’ясному скотарстві та обґрунтовано мало витратну технологію утримання м’ясної худоби без використання приміщень. У технологічному процесі передбачили екстремально різкі коливання температури довкілля, за яких доцільно застосовувати пасовищний метод утримання тварин, мати резервні запаси силосу або сінажу, мати площі для однорічних та багаторічних трав, які за необхідності слід використовувати як зелену масу або для заготівлі сіна. За зниження врожайності пасовищ необхідно підгодовувати корів силосом (10 кг), концентратами (0,5–1,5 кг), сіном (2–2,5 кг), телят відповідно – концентратами (0,5–1,0 кг) та якісним сіном (0,5–1,0 кг). За наявності зеленої маси телятам необхідно згодовувати її у кількості 5–10 кг залежно від віку, а коровам від 35 до 45 кг. Підстилку із соломи щодобово на голову вносити до 7 кг, замінити силос на сінаж та збільшити його у раціоні до 25 кг, сіна – до 7 кг. У разі зменшення температури нижче –20 °С на кожні –5 °С необхідно збільшувати в раціоні концентратів на 1 кг. Розроблені схеми і розміри зон для відпочинку, напування та годівлі тварин, прибирання та утилізації гною. Розроблені нормативи використання пасовищ за різних способів їх обслуговування та технологічні карти. Запропоновано основні параметри способів утримання м’ясної худоби, об’ємнопланувальні і технологічні рішення легкозбірних приміщень, вигульних майданчиків, технологію випасання худоби та науково обґрунтовано систему її годівлі. Розроблені та узагальнені поопераційні технологічні карти з утримання м’ясної худоби в зимовий і літній періоди. Запропонована ресурсоощадна технологія без використання приміщень та з застосуванням пасовищ в умовах східного регіону України є ефективною. Рівень рентабельності вирощування молодняку абердин-ангуської породи на м’ясо складає 155,9 %, а на племінний продаж – 254,5 %
The thesis for a Doctor’s Degree in Agricultural Sciences in 06.02.04 specialty «Livestock Production Technology». National University of Life and Environmental Science. Kyiv, 2018. Filling the Ukrainian food market with high-quality domestic beef and the competitive export access of these products should be one of the priority tasks of the agro-industrial complex. The dissertation is devoted to the substantiation of resourcesaving technology of beef production with the use of the Aberdeen-Angus in the eastern region of Ukraine. The analysis of the technology of keeping beef-producing animals in Ukraine indicates its imperfection, high production costs with the use of hard-wall rooms, energy and material resources. In this regard, a number of theoretical and practical provisions for the production of beef in meat cattle breeding have been revised, and a low-cost, resource-saving technology for outdoor keeping of beef-producing animals has been substantiated. The process stipulates extremely sharp fluctuations of ambient temperature which greatly affect the yield of pasture and the productivity of cattle. In order to prevent such fluctuations, it was proposed to apply a pasture method of keeping animals, to have spare silos or haylage reserves, and allocate areas for annual and perennial grasses in cropping pattern which, if necessary, should be used as a green mass or for harvesting hay. In case of reduction in pasture yields, it is necessary to feed cows with silage (10 kg), concentrates (0,5 to 1.5 kg), hay (2–2.5 kg), and calves respectively with concentrates (0,5-1,0 kg) and high quality hay (0.5–1.0 kg). In the presence of green mass, it should be fed to calves in the amount of 5–10 kg depending on the age, and to cows in the amount of 35 to 45 kg. To minimize the influence of critically low temperatures, rain and cold wind, it is suggested to create more comfortable conditions for keeping livestock by applying beds of straw of up to 7 kg per head, replacing silage with the haylage and increasing it in the diet up to 25 kg per head, and hay up to 7 kg. In the case of temperature drop below –20 °C, it is necessary to increase the amount of concentrated feedstuff in the diet by 1 kg/head/day for every –5 °С. To reduce the production cost of beef at the expense of maximum realization of cattle productivity, it is suggested to use tents and open areas which reduce the cost of cattle stall. The schemes and sizes of zones for rest, watering and feeding animals, cleaning and utilization of manure have been developed. Aberdeen-Angus young stock has minimal differences of constitutional types. There is only a slight (4.0–6.3 %) advantage of calves of British origin as to the fluff ratio. It can increase the heat protection of animals in winter and reduce the heat resistance of organisms in summer. It has been ascertained that the natural resistance of an organism depends on the origin, age, sex of livestock and environment conditions. Aberdeen-Angus bull calves and heifer calves can be characterized as animals with well-developed natural resistance. Thus, home young stock outperforms their peers of British origin by almost every measure of natural resistance. In the winter period, bull calves of domestic origin dominate their peers of British origin in bactericidal activity by 2.1 %, and heifer calves by 2.6 % in summer and by 2.8 % in winter. According to lysozyme activity of blood serum, bull calves of domestic origin in both seasons tend to outperform those of British breeding by 1.3 %, and heifer calves – by 1.3 % in summertime and by 0.6 % in winter. According to the phagocytic activity of neutrophils, bull calves of domestic origin dominate over their peers by 18.6 % in the summer. In winter, the prevalence of this indicator by 14.9 % is observed in bull calves of British breeding. Heifer calves of domestic origin tend to increase their phagocytic activity, compared to their peers of the British breeding, by 1.6 % in summer and by 1.9 % in winter. The resistance and adaptation of the Aberdeen-Angus young stock of British and domestic origin are high in both seasons. This testifies to their good adaptability to the system of a year-round outdoor keeping in the east of Ukraine. Studies have shown that animals, especially of small, compact type, are not competitive in market conditions. Therefore, the creation of a competitive Ukrainian beef breed should be carried out as pure breeding and with the absorption of the Aberdeen-Angus of small fast-growing type, which is spread in Ukraine, by large type Angus of American breeding. The proposed resource saving technology of outdoor keeping and using pasture in the conditions of the eastern region of Ukraine is cost-effective both for the use of Aberdin-Angus young stock for meat and for breeding with a low cost of 1 centner of gain. During the rearing period, 435.8 kg of gain have been obtained from one head when the weight of newborns is 27 kg. The production costs for rearing one head make up 6528.31 UAH when the cost of one centner of gain is 1.498 UAH. Profit from the sale of livestock for meat at a price of 36.11 UAH per 1 kg of live weight is 10183.4 UAH, while profit from the sale for breeding at a price of 50.0 UAH/kg of body weight is 16611.7 UAH. The level of profitability of rearing the AberdeenAngus young stock for meat is 155.9 %, and for breeding is 254.5 %
Keywords: м’ясне скотарство; ресурсоощадна технологія; утримання худоби без приміщень; пасовищний період; створювана українська ангуська м’ясна порода; meat cattle breeding; resource-saving technology; outdoor keeping